Identifying qualitative differences in PPARα signaling networks in human and rat hepatocytes and their significance for next generation chemical risk assessment methods. (April 2020) - McMullen, Patrick D.; Bhattacharya, Sudin; Woods, Courtney G.; Pendse, Salil N.; McBride, Mary T.; Soldatow, Valerie Y.; Deisenroth, Chad; LeCluyse, Edward L.; Clewell, Rebecca A.; Andersen, Melvin E.
Abstract: In this paper, we evaluate the PPARα signaling network in rats, examining transcriptional responses in primary hepatocytes exposed to a PPARα specific ligand, GW7647. These transcriptomic studies were complemented with ChIP-seq studies of PPARα binding and transcription binding motif identification for PPARα responsive genes. We also conducted a limited study of GW7647 dosing the in intact rat to examine differences in transcriptional responses for primary hepatocytes in vitro and in the intact liver. The rat network has a much larger number of down-regulated genes and pathways than we had found in the human and the PPARα binding motifs in rat differed for upregulated and down regulated genes. Based on these results and comparison with our previous work with the human PPARα signaling network, we identified qualitative differences in the transcriptional networks controlled by PPARα activation in the two species that provide an explanation of the interspecies differences in the responses of humans and rodents to GW7647 and likely to other PPARα agonists. These studies also allow some observations on the manner in which in vitro, fit-for-purpose assays in human hepatocytes could form the basis for risk assessment without recourse to in-life studies in rodents or other test species. Highlights: We evaluated signaling networks for PPARα in human and rat primary hepatocytes. Using gene expression and ChIP profiling, we found qualitative differences in the PPARα networks. Extensive downregulation of PPARα pathways in the rat hepatocytes correlated with proliferation in the liver. We discuss approaches for risk assessment using just the in vitro study results with this nuclear receptor pathway.